Sources and rates of phosphorous fertilizers in soybean crops cultivated on cerrado soils - Fernandes, Francisco Maximino; Ferreira, Manoel Evaristo; Mello, Francisco de A.F. de (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1984)
The present work was held in Dark-Red Latosol of the Experimental Farm of UNESP - Campus of Ilha Solteira, in Selvíria (MS). In the first crop three sources of phosphorus (triple superphosphate, Mg-thermophosphate and phosphate fro were applied in broadcast followed by incorporation into the soil, in the rates of 145-290-435-580 kg/ha of total P2O5. A control treatment with no addition of phosphorus was included. In the second crop it was studied the residual effect of the fertilizers appied to the first crop and the effect of five maintenance rates of phosphorus (0-36-72-108- 144 kg/ha of P2O5) applied as triple superphosphate in the furrow. It was observed a significant response of the crop the phosphated fertilization. The Mg-termophosphate and the triple superphosphate had similar behavior in the first crop, the former superior to this fertilizer respect to the residual effects. The phosphate from Araxá showed and efficiency of 80% as compared to the triple superphosphate either, withor without maintenance fertilization. So, the phosphate from Araxá can be recomended for corretive fertilization of soils of low fertility.